METHODS AND SYSTEMS FOR AD PLACEMENT PLANNING - CHEN DONGNI; NAGARAJAN CHANDRASHEKHAR; KALE SATYEN; CHEN PEIJI; MANDALAPU SRINATH; VEE ERIK (2013)
Methods and systems are disclosed which allow shifting inventory to fulfill guaranteed delivery advertisement contracts. Inventory may be allocated from a supply of unallocated inventory to one or more advertisers in accordance with guaranteed delivery agreements. Inventory may be reserved for the one or more advertisers from the remaining supply of unallocated inventory. Inventory may then be allocated to an additional advertiser by using unallocated inventory or shifted inventory, or a combination of unallocated inventory and shifted inventory. The shifted inventory is shifted out of the allocation for the first advertiser and the shifted inventory is replaced by the reserve inventory for the respective advertiser.